Phytomass and production components of colored cotton under salt stress in different phenological stages - Lauriane A. dos A. Soares; Pedro D. Fernandes; Geovani S. de Lima; Saulo S. da Silva; Rômulo C. L. Moreira; Thamara L. F. Medeiros (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Scarcity of good quality water is a limiting factor for irrigated agriculture, especially in semi-arid regions, which induces the use of waters with high salt concentration in crop irrigation. In view of the above, the objective of this study was to evaluate the phytomass accumulation and production components of colored cotton genotypes during the different development stages, under conditions of high salinity, with plants grown in lysimeters under greenhouse conditions, at the Center for Technology and Natural Resources of the Federal University of Campina Grande, Paraíba, Brazil. Three cotton genotypes (‘BRS Rubi’, ‘BRS Topázio’ and ‘BRS Safira’) irrigated with salinized water (9 dS m-1) during the three stages of crop development (vegetative, flowering and fruiting) were evaluated. The experiment was conducted in a randomized block design with three repetitions and three plants per plot, in drainage lysimeters filled with 24.5 kg of an Oxisol, with sandy loam texture. Irrigation with salinized water during the vegetative stage promoted greater phytomass accumulation in the genotypes of naturally colored cotton. In the initial stages of the cotton development, irrigation with saline water can be used with the lowest losses in production components, which are negatively affected when saline water is applied in the fruiting stage. Among the genotypes, ‘BRS Topázio’ is the most tolerant to irrigation water salinity in terms of seed cotton weight and lint cotton weight, regardless of the development stage.